Impact of a specialised 'birth after caesarean section (BAC)' clinic. (7th June 2011) - Harlow, F; Dunlop, K; Bircher, C; Simpson, P; Tinsley, J
Abstract : Background: Multiple caesarean sections (C/S) have an impact on maternal morbidity and are 'resource hungry'. Previous audit data (April 2008–October 2009) in this unit had shown that 44% of elective C/S were performed for 'maternal request' after the woman had one previous C/S. Consequently a birth after caesarean (BAC) clinic was set up where the care of women was standardised. This is Consultant led with a specialised midwife and patient information leaflets. Aims: To increase the percentage of women opting for Vaginal (V) BAC resulting in an increased percentage of successful VBAC's without increasing the overall complication rate from VBAC. To standardise an induction of labour (IOL) protocol for VBAC's to improve the success rate further. Standards: The delivery register was reviewed for 6 months prior to the BAC clinic (November 2009–April 2010): 40% of women with one previous C/S aimed for VBAC with a 64% success rate. Results: 93 women have delivered via the BAC clinic between May-December 2010. 73% opted for VBAC of which 68% were successful. 10 women chose IOL and 3 had emergency C/S. One woman had an incidental finding of scar dehiscence in spontaneous labour. Seven babies went to NICU – 6 after emergency C/S and 1 after SVD; 4 of these infants were preterm. Conclusions: There was a significant improvement in the percentage of women opting for VBAC. There was a more modest improvement in VBAC success rates which we hope will be sustained as more data becomes available. We will continue monitoring complication rates.